Beginning EJB 3 Application Development - Kodali, Raghu R. (Apress, 2012)
While only few names are mentioned here, I must say that I’ve been lucky enough to have a strong team with representation from friends, family, colleagues at work, and special people from the publishing house. Without this swat team, we would still only be thinking about the book. I would like to thank my friend Peter Zadrozny, who encouraged and convinced me that I could do this book, and who introduced me to Apress. Without his experience, craft, and guidance, this book would not have been possible. Thanks to Sofia Marchant, Damon Larson, and Kelly Winquist at Apress, for being patient and helping us through the process of putting our chapters together and making it all happen. It is tough to work on a book when you have a day job to take care of. Thanks to my manager Roel Stalman for encouraging me to take on this book project and keeping keen interest.